BUILDING TOURIST LOYALTY THROUGH A WELLNESS TOURISM APPROACH IN NORTH LOMBOK REGENCY - Mawar Junita (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the role of wellness tourism in fostering tourist loyalty in North Lombok Regency. Wellness tourism has emerged as a growing tourism trend that emphasizes tourists’ physical, mental, and spiritual well-being through various activities such as yoga, meditation, spa treatments, and nature-based therapies. This research employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation involving 10 informants consisting of tourism business actors, government representatives, tourists, and local community members. The findings indicate that North Lombok Regency possesses significant potential for the development of wellness tourism based on its natural resources and local cultural heritage. Holistic tourism experiences were found to enhance tourist satisfaction and emotional attachment, which in turn contribute to tourist loyalty and revisit intention. Furthermore, collaboration among stakeholders, service quality improvement, and the implementation of sustainability principles were identified as key factors in strengthening tourist loyalty. This study provides practical implications for the development of sustainable and competitive wellness tourism destinations.